Near-Infrared Assessments of Skeletal Muscle Oxidative Capacity in Persons With Spinal Cord Injury - Erickson, Melissa Lynn (2013)
PURPOSE: After spinal cord injury (SCI) skeletal muscle decreases in size, increases in intramuscular fat, and has potential declines in mitochondrial function. Reduced mitochondrial function has been linked to the development of metabolic disease. The aim of this study was to measure mitochondrial function in persons with SCI using near-infrared spectroscopy (NIRS). METHODS: Oxygen consumption of the vastus lateralis muscle was measured with NIRS during repeated short-duration arterial occlusions in nine able-bodied (AB) and nine persons with motor complete SCI. Skeletal muscle oxidative capacity (Vmax) was evaluated with two approaches: (1) rate constant of the recovery of oxygen consumption after exercise and (2) extrapolated maximum oxygen consumption from a progressive work test. RESULTS: Vmax as indicated by the rate constant (k) from the recovery kinetics test was lower in SCI compared to AB participants (k: SCI: 0.7 ± 0.3 vs. AB: 1.9 ± 0.4 min(−1); p < 0.001). Time constants were SCI: 91.9 ± 37.8 vs. AB: 33.6 ± 8.3 sec. Vmax from the progressive work test approached a significant difference between groups (SCI: 5.1 ± 2.9 vs. AB: 9.8 ± 5.5%Hb-Mb/sec; p = 0.06). CONCLUSIONS: NIRS measurements of Vmax suggest a deficit of 50-60% in participants with SCI compared to AB controls, consistent with previous studies using (31)P-MRS and muscle biopsies. NIRS measurements can assess mitochondrial capacity in people with SCI, and potentially other injured/diseased populations.